2020
DOI: 10.3390/v12111319
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sub-Lineage of Chikungunya Virus East/Central/South African Genotype Indian Ocean Lineage Caused Sequential Outbreaks in Bangladesh and Thailand

Abstract: In recent decades, chikungunya virus (CHIKV) has become geographically widespread. In 2004, the CHIKV East/Central/South African (ECSA) genotype moved from Africa to Indian ocean islands and India followed by a large epidemic in Southeast Asia. In 2013, the CHIKV Asian genotype drove an outbreak in the Americas. Since 2016, CHIKV has re-emerged in the Indian subcontinent and Southeast Asia. In the present study, CHIKVs were obtained from Bangladesh in 2017 and Thailand in 2019, and their nearly full genomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The structural protein regions in the amplified fragment were directly sequenced. The phylogenetic tree showed that the virus clustered into the previous 14 strains and other Thailand strains in the same clade of C2.3c (45), which is related to recent CHIKVs detected in Myanmar, China, and Taiwan in 2018-2019 ( Figure 2). The E1-K211E and E2-V264A mutations were present in this clade (Supplementary Table S3).…”
Section: Phylogenetic Analysismentioning
confidence: 81%
See 3 more Smart Citations
“…The structural protein regions in the amplified fragment were directly sequenced. The phylogenetic tree showed that the virus clustered into the previous 14 strains and other Thailand strains in the same clade of C2.3c (45), which is related to recent CHIKVs detected in Myanmar, China, and Taiwan in 2018-2019 ( Figure 2). The E1-K211E and E2-V264A mutations were present in this clade (Supplementary Table S3).…”
Section: Phylogenetic Analysismentioning
confidence: 81%
“…Since then, the number of cases rapidly increased across the country and surged in Bangkok (21). Based on phylogenetic analysis, the recent CHIKVs circulating 2016-present, particularly in India, Pakistan, Bangladesh, and Thailand, were classified as belonging to the new IOL sub-lineage of genotype ECSA with specific amino acid mutations of E1-K211E and E2-V264A (45). The present study showed that the 23 CHIKVs collected in October 2019 were closely related to CHIKVs from southern Thailand collected earlier in late 2018 and recent circulating strains in 2019 from Myanmar, China, and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen nearly whole CHIKV genomes from infected patients were sequenced and the genotypes determined in a previous study [ 52 ]. We were able to amplify the CHIKV structural protein gene regions from the sera of an additional 9 patients, though we failed to do so in the remaining 3 patients, probably due to low amounts of the virus within the sera ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%